Intraday Volatility in International Stock Index Futures Markets: Meteor Showers or Heat Waves? - Booth, G. Geoffrey; Chowdhury, Mustafa; Martikainen, Teppo; Tse, Yiuman (Management Science, 1997)
The international transmission of intraday price volatility among the United States, United Kingdom, and Japanese stock index futures markets in the period 1988–1994 is investigated in this paper. The empirical results based on extreme-value estimators and vector autoregression indicate the rapid transmission of information between markets. The volatilities of the U.S. and U.K. futures markets appear to follow a meteor shower rather than a heat wave type of process. This means that these volatilities react to shocks from other markets, i.e., they cannot be described only by their past values. However, the heat wave hypothesis is not rejected for the Japanese market, meaning that the shocks to Japanese volatility are mostly country-specific. A multivariate GARCH model supports the U.K. and Japanese but not the U.S. results.